Filariasis malayi in Pondok Village, West Umbu Ratunggay, Central Sumba Regency - Soleman Landi; Tri Baskoro T Satoto; Soeyoko Soeyoko (Tropical Medicine Journal, 2012)
ABSTRACTIntroduction: Lymphatic filariasis is a communicable disease that still cause public health problem include in Sumba Island, East Nusa Tenggara Province. The cause of disease is three species of filaria and had been distributed almost in all area of Indonesia. There are differences in the distribution of species in the Indonesian regionObjectives: To investigate the profile of filariasis, the species and Microfilaria rate in Pondok Village.Methods: The sample was all of population in Pondok Village who meet the criterion and examination was performed by observation and fingerprick blood survey.Results: Fingerprick blood survey was performed on 500 respondents and was found 23 respondents suffered microfilaremia. Based on their clinical symptoms it was found 45 respondents had acute limfangitis symptoms, headache and frequent relapse fever (10 was positive mikrofilaremia) and 4 respondents suffered chronic symptoms. Based on the microfilaria morfology identification it was known that all of the filariasis caused by Brugia timori species.Conclusion: Pondok Village was lymphatic filariasis endemic area, caused by Brugia timori with microfilaria rate at 4,6%.Keywords : Filariasis, Microfilaria rate, Brugia timori, Sumba Island.